Utility of device-derived daily activity, a novel digital biomarker, to predict ventricular arrhythmias – data from the CERTITUDE registry. (14th October 2021) - Kutyifa, V; Rosero, S; Harrel, C; Singh, J; Hicks, J; Chinitz, L; Varma, N; Piccini, J; Turakhia, M
Abstract: Background: While there have been prior studies showing an association between activity and outcomes, there have been no studies examining the temporal relationship between device-derived daily activity, a novel digital biomarker, and ventricular tachyarrhythmias (VT). Purpose: In a big dataset with over 55, 000 pacemaker, ICD, and CRT devices, we aimed to identify whether changes in activity predict VT, or else VT predict changes in activity. Methods: The CERTITUDE registry comprises a de-identified database of over 55, 000 U.S. BIOTRONIK pacemaker, ICD, CRT devices, and loop recorders active on Home Monitoring®. Daily data on leads, arrhythmias, and physiological parameters such as activity are captured. Patient activity is reported daily as percentage active during the day, assessed by a one-axis accelerometer at ∼0.4 Hz frequency. Analysis to ascertain temporal changes in device-derived activity associated with treated VT was performed using the first event per device and 7-day activity windows (baseline, pre- and post-event). Baseline period was defined as 31–38 days prior to VT. VT events were categorized by heart rate (≤200 bpm, >200 bpm) and treatment (shock with or without ATP, ATP alone). Differences in activity between baseline, and pre- and post-VT were analyzed using the binomial proportion test. Results: A total of 16, 475 devices (9732 ICDs, 6743 CRT-Ds) had activity data available for analysis. The cumulative follow-up duration was 18, 355 years (5.6 million days with transmission). Of the 2636 VT events analyzed, 1409 had a heart rate >200 bpm, and 593 were treated with shock. Patients with VT events >200 bpm treated with shock had a significant reduction in activity post-VT with a median −8.7% reduction (IQR −24.6%; 7.3%, p<0.001). However, there was no reduction in activity before the VT>200 bpm (p=0.690) (Figure). VT events >200 bpm treated with ATP alone were not associated with reduction in activity before or after the episode. Similarly, VT events ≤200 bpm treated with shock were also associated with a reduction in activity following the event (−5.8%, IQR −29.5, 12.3%, p=0.003), but not prior to the VT event. Conclusions: In this report from the CERTITUDE registry, we have shown a temporal decline in device-derived activity following ventricular arrhythmias>200 bpm and ≤200 bpm treated with a shock, but not in patients treated with ATP. Monitoring device-derived activity post-VT events with a shock could provide relevant clinical information and potentially warrant intensified treatment. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Biotronik